Simulation of space charge in electric double layer capacitor - Abdul Rahman, Arif Farhan (2015)
Electric double layer capacitor (EDLC) is one of the super capacitors families. Due to its high power density compared to lithium battery, EDLC has been widely applied in much modern application such as in electric or hybrid cars and aircraft emergency doors. During its operation, charges are being stored electrostatically onto an interface layer between its actives electrode and electrolyte, resulting fast charging-discharging and long-life energy storage device. Charge behavior inside an EDLC can be well-studied based on ac impedance and space charge measurement. Nonetheless, the numbers of scientific researches dealing with the space charge measurement on EDLC are very limited in the past decade. This research project aims to investigate the space charge behavior in EDLC using Quickfield software. The charge and potential distribution within an EDLC were simulated and analyzed in this project